MELATONIN PREVENTS APOPTOSIS IN BRAINS OF NEONATES INDUCED BY MATERNAL HYPOTHYROIDISM - Hidayat, Mariyah; Chaudhry, Shire; Salman, Sahal; Lone, Khalid Pervez (Journal of Ayub Medical College Abbottabad, 2019)
Background: Loss of motor neurons may underlie some of the deficits in cognitive functions associated with maternal hypothyroidism during fetal and neonatal period. This experiment was performed to highlight the significance of melatonin intake by the mother in hypothyroid state during gestation and lactation to preserve the integrity of motor neurons in the newborns. Methods: Twelve female Wistar rats were divided equally into four groups, including control (A), hypothyroid (B), melatonin treated hypothyroid (C) and only melatonin treated (D) groups and allowed to conceive. For inducing hypothyroidism, Propylthiouracyl (PTU) was administered in a dose of 15mg/kg/day orally mixed with chow a week before mating and throughout the period of gestation and weaning up till 22nd day after delivery. Melatonin was given in a dose of 10mg/kg/100ml of drinking water. After delivery, 10 neonatal rats from each group were sacrificed on 22nd day of life and blood samples were immediately collected for evaluating serum levels of T3, T4 and TSH. The freshly extracted brains were sliced into two equal parts from the midline. One half was instantly immersed in ice cold phosphate buffered saline and homogenized for extraction of RNA to determine the genetic expressions of caspases 3, 8 and 9. Other half of the brain was instantly immersed in 10% formalin for 2 weeks. After processing of the brain tissue, 5 Î¼m thick sections were sliced and transferred to albumin coated glass slides. They were later stained by Nissl staining technique, visualized and photographed under a research microscope for signs of apoptosis. The mRNA and protein levels of caspase-3, 8, and 9 were analyzed using a real-time RT-PCR. Results: Serum enzyme analysis showed that the pups of dams taking PTU were severely hypothyroid and melatonin treated rats showed significant restoration of serum thyroid hormone levels. Features of apoptosis and disturbed migration of cells was seen in B group as compared to C group and mRNA levels of caspase-3 and 9 were increased significantly in B group. Conclusion: Melatonin helps to maintain neuronal function in hypothyroid newborn rats by inhibiting apoptosis and improving survival. Keywords: Hypothyroidism; melatonin; propylthiouracil; hippocampus; pyramidal neurons; Caspases